Recent advances in the treatment of traumatic brain injury with autologous and non-autologous multipotent stem and progenitor cells: preclinical models and clinical trials - Alizada, Mujahid; Lin, Shu; Gao, Hongzhi (Folia Neuropathologica, 2021)
Traumatic brain injury (TBI) is a global health issue which causes millions of deaths and disabilities every year. The survivors of TBI may suffer from sensorimotor dysfunction, memory and cognitive disturbances, hearing and vision deficits, and various psychological problems. The primary insult may damage neurons, cerebral vessels and the blood-brain barrier, causing reactive astrogliosis and immune response with further damaging consequences. TBI lacks effective therapy. The currently available clinical treatment options include hyperbaric oxygenation, brain stimulation and rehabilitation. In recent years, the research on stem cell treatment of TBI has received extensive attention. Various types of stem cells, such as four types of mesenchymal stem cells, neural stem cells and olfactory ensheathing cells have been tried to treat TBI in clinical trials and preclinical models. This article reviews the research of autologous and non-autologous multipotent stem and progenitor cells for the treatment of TBI in both clinical and preclinical settings.